PENGARUH AKTIVITAS BELAJAR SISWA DALAM MODEL PEMBELAJARAN KOOPERATIF TERHADAP HASIL BELAJAR GEOGRAFI DI SMAN 1 CEPIRING KABUPATEN KENDAL - Taqorrub Ubaidillah (Institut Agama Islam Negeri Ponorogo, 2020)
The research was done at SMAN 1 Cepiring in 2020. The purpose of this study is 1) To determine the level of student learning activities in the cooperative model of geography learning in SMAN 1 Cepiring in 2020, 2) To find out how much influence the learning activities of students in the cooperative model on geography learning outcomes at SMAN 1 Cepiring in 2020. Population in this study were all students of class X SMAN 1 Cepiring consisting of six classes in the academic year 2019/2020. The sampling technique uses a random sample by using a lottery (random sampling) because the class is considered homogeneous and the selected class X-1 and X-2. The variables measured were student learning activities in cooperative learning models and geography learning outcomes. Analysis of the data used is descriptive analysis of percentages and multiple regression analysis. The results obtained by the description that the activities of students in the cooperative learning model in the high category. Whereas for testing the hypothesis through multiple regression analysis the results obtained are that there is a significant influence between student learning activities in the cooperative learning model of learning outcomes in geography, in this case the effect is in the high category.